Variation in maternal provisioning by lactating Antarctic fur seals ( Arctocephalus gazella ):response to experimental manipulation in pup demand - Arnould, J.; Boyd, I.; Rawlins, D.; Hindell, M. (Behavioral Ecology and Sociobiology, 2001)
An experiment involving the supplementary feeding of pups was conducted on Antarctic fur seals to investigate the factors influencing maternal foraging-attendance cycles and the differential use of nutritional resources for growth, maintenance and storage by pups. For 40% of the lactation period, male pups were given a supplement mimicking the chemical composition of Antarctic fur seal milk at a dose equivalent to 35% of the normal mass-specific milk energy intake for the species. Milk consumption, body composition and growth rates were monitored during and after the supplementary feeding period and maternal foraging-attendance cycles were monitored throughout lactation. During the supplementary feeding period, treatment pups (n=8) grew 32% faster and deposited greater adipose tissue stores than controls (n=8) but consumed the same amount of maternal-delivered milk. When supplementary feeding was stopped (timed to coincide with peak maternal milk yield in this species), treatment pups lost mass whereas control group pups continued to grow. Treatment pups weaned at a younger age (109 days) than control pups (116 days) but at the same mass (13 kg). Maternal attendance durations did not differ between the treatment and control groups throughout lactation. However, mothers of treatment pups had significantly shorter foraging trip durations (3.74 days) than mothers of control pups (4.74 days) during the period of supplementary feeding (there were no significant differences throughout the rest of lactation). These findings are in accordance with predictions of a marginal-value model of fur seal lactation behaviour.